Exploring the effect of cool and hot EFs training in four-year-old children. Issue 5 (3rd September 2021) - Pellizzoni, Sandra; Fontana, Martina; Passolunghi, Maria Chiara
ABSTRACT: Executive Functions (EFs) are crucial top-down processes characterized by cool and hot aspects, required for goal-directed behaviour. Only a few studies evaluated and trained concurrently cool and hot EFs. Therefore, we promote a training aiming to enhance both EFs components. A total of 91 children attending the second year of kindergarten were involved. Forty-two children attended the EFs training, while forty-nine children represented the active control group. The training was proposed twice a week for three months. The twenty sessions were divided as follows: 10 were focused on cool EFs, while the last 10 were related to hot EFs. The children were evaluated before and after the trainings with tasks including inhibition, working memory, delay of gratification, and emotion regulation. The results indicate increased cool and hot EFs abilities in children who attended the EFs training. Data are discussed in terms of developmental implications and highlights the importance to promote training focused also on hot EFs aspects.